Volcano wakes up! - Peters, Lisa Westberg; Jenkins, Steve, 1952- (New York : Holt, 2010)
The influence of a volcanic eruption on the surrounding land and forms of life is examined from the perspectives of a volcano, ferns, a cricket, a small black road, and the sun and the moon.
Includes bibliographical references.
Publisher's Weekly
School Library Journal
Wilson's Children
Booklist, March 2010
Horn Book, October 2010
Keywords: Children's poetry, American; Volcanoes -- Juvenile poetry; American poetry; Volcanoes -- Poetry; American poetry; Volcanoes -- Poetry; Picture books for children